2014
DOI: 10.3324/haematol.2014.108472
|View full text |Cite
|
Sign up to set email alerts
|

Successful change of treatment strategy in elderly patients with primary central nervous system lymphoma by de-escalating induction and introducing temozolomide maintenance: results from a phase II study by The Nordic Lymphoma Group

Abstract: lymphomas (DLBCL) and it was previously shown that the addition of rituximab to CHOP chemotherapy has improved the prognosis in DLBCL outside the brain. 8 2) The intraventricular MTX/cytarabine treatment of the Bonn protocol requiring an Ommaya reservoir was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 31 publications
4
61
1
Order By: Relevance
“…Based on a recent systematic review, 7 only few prospective multicentre studies focussing on elderly patients with PCNSL have been reported, 14, 15, 16, 17, 18, 19, 20 which all used HD-MTX-based chemotherapy. However, no standard protocol has yet been defined and there was no study that used rituximab.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a recent systematic review, 7 only few prospective multicentre studies focussing on elderly patients with PCNSL have been reported, 14, 15, 16, 17, 18, 19, 20 which all used HD-MTX-based chemotherapy. However, no standard protocol has yet been defined and there was no study that used rituximab.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12]19,22 In a multicentre retrospective analysis investigating patients with a median age of 52.4 years undergoing HDT-ASCT as salvage therapy, the 5-year survival rate of patients with chemosensitive relapse was 62%. 13 In another large retrospective analysis investigating patients with a median age of 54 years undergoing HDT-ASCT as first-line treatment, the reported 2-and 5-year survival rates were 82% and 79%, respectively.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Based on a recent systematic review, 9 a limited number of prospective multicentre studies focussing on elderly PCNSL patients has been reported. 8,[17][18][19][20][21] Most of the studies included HD-MTX in combination with partner chemotherapy agents, but to-date no standard protocol has been defined. Acknowledging the limitations of intertrial comparison, the best reported response rate was 79% but the corresponding 1-year PFS was only 36%.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Nine of the 14 studies dedicated to elderly patients [7, 12, 25, 26, 28-32] were retrospective, and 4 were phase II studies [4, 5, 9, 27], with one of them designed as a randomized phase II study [4]. Six studies that reported on elderly subgroups were phase II studies [6, 14-16, 34, 35], and 1 was a retrospective analysis of elderly patients in a phase III study [13]. Treatment regimens varied from monotherapy to multidrug HD-MTX-based combinations.…”
Section: Diagnosis and Treatment Of Elderly Patients With Pcnslmentioning
confidence: 99%
“…Fourteen studies were dedicated to elderly patients [4, 5, 7, 9, 12, 24-33], and 7 studies accrued adult patients of all ages but contained information on outcome of the elderly subgroup [6, 13-16, 34, 35]. One retrospective study [3] described the outcome of thiotepa-based chemotherapy with ASCT administered to 52 elderly lymphoma patients, of whom 15 were PCNSL treated by this protocol as first-line approach.…”
Section: Diagnosis and Treatment Of Elderly Patients With Pcnslmentioning
confidence: 99%